2020
DOI: 10.1590/1980-0037.2020v22e55697
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric characteristics and physical performance of taekwondo athletes

Abstract: The purpose of this investigation was to measure anthropometric and physical performance variables of TKD athletes from the city of Pelotas - RS. Forty-five athletes aged 16.4 ± 5.2 years and time of practice of 3.25 ± 3.6 years were evaluated. Athletes performed anthropometric evaluation and physical, general and specific performance tests. In the sum of seven skin folds, men presented lower values ??(106.1 ± 49.5 mm versus 143.4 ± 43.2 mm, p <0.002). Male seniors presented better performance in the vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…Furthermore, in our ndings, the anaerobic strength index measured by the vertical jump test is only effective in the performance of male athletes. The same phenomenon happens in the previous study (Formalioni et al, 2020) in which men, when compared to women, performed higher vertical jumps with greater anaerobic power.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, in our ndings, the anaerobic strength index measured by the vertical jump test is only effective in the performance of male athletes. The same phenomenon happens in the previous study (Formalioni et al, 2020) in which men, when compared to women, performed higher vertical jumps with greater anaerobic power.…”
Section: Discussionsupporting
confidence: 86%
“…To the best of our knowledge, this is the first study that has morphological characteristics of the medalist and non-medal elite taekwondo athletes at the European championship level. Anthropometric characteristics (Formalioni et al, 2020), body fat percentage, and body fat mass are used as basic data to, directly and indirectly, evaluate the performance of athletes (Kim et al, 2015). Taekwondo is also a weight division game: the physical characteristics of athletes are a critical factor of winning or losing (Kim et al).…”
Section: Discussionmentioning
confidence: 99%
“…19 Long extremities are often advantageous in striking sports, like combat sports, and studies have shown correlations between limb length and Wushu performance. 19,20 After an 8-week Wushu training program, significant improvements were observed in anthropometric measurements, including shoulder anterior-posterior distance, thigh circumference, calf circumference, biceps circumference, hip circumference, intermalleolar distance, interstyloid distance, interpicondylar distance, and intercondylar distance. This suggests that Wushu enhances body composition and may be particularly beneficial for athletes with specific limb characteristics.…”
Section: Discussionmentioning
confidence: 99%